The Fascist experience in Italy - Pollard, John F. (John Francis) 1944- (Routledge sources in history., 1998)
This book examines the development of Italian Fascism, and surveys the themes and issues of the movement. Beginning with the emergence of the united Italian state, sources go on to cover the political, social and economic status of Italy in the nineteenth century and the post-war aftermath of Fascism. The Fascist Experience in Italy provides analysis of printed and broadcast propaganda, as well as Mussolini's journalism and an extensive range of other source material, including images. The author includes new documentary material, previously unavailable in English, and thematic coverage of major topics such as the transformation of Italian agrarian and urban society and the actions of the Papacy.